2001
DOI: 10.1046/j.1365-2257.2001.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of ambulatory DVT management using a multidisciplinary approach*

Abstract: Low molecular weight heparins (LMWHs) have been demonstrated to be at least as safe and effective as unfractionated heparin (UFH) in the initial management of deep vein thrombosis (DVT). However, the effectiveness of using LMWH in the ambulatory management of DVT in a 'real-life' setting has yet to be evaluated. This multicentre retrospective study involving 697 patients considers the outcome data of patients under- going ambulatory DVT treatment with tinzaparin (Innohep(R), Leo Pharmaceuticals, Risborough, Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Treatment with low molecular weight heparin enables ambulatory treatment of DVT in most patients reducing the number of patients referred to tertiary hospital care in recent years. 15 We acknowledge the limitations of this retrospective study as the number of patients is small and the lack of long-term (5 to 10 year) follow up prevents conclusions about the durability of this treatment. Multicentre studies will be required to answer open questions and to define optimal treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Treatment with low molecular weight heparin enables ambulatory treatment of DVT in most patients reducing the number of patients referred to tertiary hospital care in recent years. 15 We acknowledge the limitations of this retrospective study as the number of patients is small and the lack of long-term (5 to 10 year) follow up prevents conclusions about the durability of this treatment. Multicentre studies will be required to answer open questions and to define optimal treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have demonstrated that low molecular weight heparin, given by once daily subcutaneous injections, has superior efficacy, a safer profile and greater cost efficiency than unfractionated (intravenous) heparin for deep vein thrombosis treatment (O’Shaughnessy et al, 1998; Rose et al, 2001; Turpie et al, 2002). Low molecular weight heparin, at treatment doses, has a 24 hour efficacy, which gives it great flexibility for outpatient use but is difficult around surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This concern is similar to that seen during the development of outpatient DVT management during the late 1990s, and may have influenced the ability to enter all suitable patients with PE into the present study. The initial outpatient DVT studies were interpreted with caution, but further studies confirmed both the safety and acceptability of outpatient DVT management, permitting f91% of patients to be managed without admission [10,11,14,23]. As a significant proportion of patients with DVT also have silent PE (as defined by high-probability V'/Q' scans) [3][4][5][6], it is likely that many patients who receive outpatient treatment for DVT have also received outpatient treatment of PE.…”
Section: Discussionmentioning
confidence: 99%
“…The management of VTE is now well established, with an initial period of treatment with subcutaneous low molecular weight heparin (LMWH) followed by a variable period of oral anticoagulation therapy. As some LMWHs may be administered as a once-daily subcutaneous injection and do not require coagulation monitoring, most patients with confirmed DVT now receive outpatient anticoagulation therapy organised by teams of specialist nurses [7][8][9][10][11]. As PE is part of the same disease process, it may be possible to extend outpatient management to selected low-risk patients, in contrast to the current situation, where the vast majority of patients remain as in-patients until oral anticoagulation is established.…”
Section: ++mentioning
confidence: 99%